Urine volume and residual renal function decline among patients on peritoneal dialysis - searching for associations - Macau,Ricardo A (2018)
Introduction: Preservation of urine volume and residual renal function in patients on peritoneal dialysis (PD) is a major concern. Some factors have been associated with better prognosis, such as the use of biocompatible solutions, furosemide, or renin-angiotensin-aldosterone system blockers. However, results from previous studies have not been consistent. We thus aimed to study the relation between baseline characteristics of incident patients on PD, treatment characteristics, glomerular filtration rate (GFR) and urine volume (UV) variation. Subjects and methods: We retrospectively analyzed incident patients on PD (first option) in our unit in terms of variation of UV and GFR after 24 months of follow-up. We studied the association between GFR and UV decline and baseline characteristics (age, gender, diabetes mellitus or hypertension diagnoses, body mass index, CKD etiology, and use of beta-blockers, diuretics, renin-angiotensin-aldosterone system blockers) as well as PD treatment characteristics (PD modality, use of icodextrin, dialysis days per week, presence of peritonitis, membrane characteristics such as Ca125 peritoneal level and dialysate-to-plasma creatinine), dwell hours per day and glucose load) using Spearman correlation for numerical variables and differences of means for binomial variables. Results: We analyzed 25 patients. Urine volume decreased on average 0.59 mL after 24 months and glomerular filtration rate declined from 7.9 to 7.03 mL/min/1.73m2. All patients used biocompatible solutions. We did not find any association between glucose-exposure, use of diuretics or renin-angiotensin-aldosterone system blockers and urine volume or glomerular filtration rate decline. There was a significant relation between diuresis and GFR changes. Discussion: Our patients present a slower decline of residual renal function than that described in the literature. Strategies to preserve diuresis, including the use of biocompatible solutions, may explain these results.